PROFIL TITER ANTIBODI Newcastle Disease (ND) dan Avian Influenza (AI) PADA ITIK PETELUR FASE GROWER DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Novia Yusmariza; Purnama Edy Santosa; Siswanto . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This study aimed to determine the antibody titre against Newcastle Disease (ND) and AvianInfluenza (AI) in laying duck of grower phase. This study has been conducted in December 2013–January 2014 in Gadingrejo Subdistrict, Pringsewu District, Lampung Province. The method used inthis study were survey method and sample collecting by method of purposive sampling. The variableobserved was the antibody titre against Newcastle Disease and Avian Influenza. The data analysisused in this study was descriptive analysis. Based on the result of Hemaglutination Inhibition (HI) onAvian Influenza in laying duck of grower phase in Gadingrejo Subdistrict, there were 33% ducks thatshowed seropositive result on AI with the score of 21, 23, 26, 27, 25 and there were 67% ducks showedseronegative. Based on the result of HI test of Newcastle Disease in laying duck of grower phase inGadingrejo Subdistrict that showed seropositive result 19% with the titre score of 23, 24 and 81%ducks showed seronegative. The level of uniformity on AI was granted the score of 33% and the levelof uniformity on ND was 19%.